Can mentorship improve laboratory quality? A case study from influenza diagnostic laboratories in Southeast Europe - Lauren Polansky; Stephanie Chester; Melissa Warren; Tricia Aden; Pamela Kennedy; Stacey Spivey-Blackford; Ann Moen (BMC, 2019)
Abstract Background Strengthening the quality of laboratory diagnostics is a key part of building global health capacity. In 2015, the Centers for Disease Control and Prevention (CDC), the Southeast European Center for Surveillance and Control of Infectious Diseases (SECID), WHO European Regional Office (WHO EURO) and American Public Health Laboratories (APHL) collaborated to address laboratory quality training needs in Southeast Europe. Together, they developed a quality assurance (QA) mentorship program for six national laboratories (Laboratories A-E) in five countries utilizing APHL international consultants. The primary goal of the mentorship program was to help laboratories become recognized by WHO as National Influenza Centers (NICs). The program aimed to do this by strengthening influenza laboratory capacity by implementing quality management systems (QMS) action steps. After 1 year, we evaluated participants' progress by the proportion of QMS action steps they had successfully implemented, as well as the value of mentorship as perceived by laboratory mentees, mentors, and primary program stakeholders from SECID and WHO EURO. Methods To understand perceived value we used the qualitative method of semi-structured interviews, applying grounded theory to the thematic analysis. Results Mentees showed clear progress, having completed 32 to 68% [median: 62%] of planned QMS action steps in their laboratories. In regards to the perceived value of the program, we found strong evidence that laboratory mentorship enhances laboratory quality improvement by promoting accountability to QMS implementation, raising awareness of the importance of QMS, and fostering collaborative problem solving. Conclusion In conclusion, we found that significant accomplishments can be achieved when QA programs provide dedicated technical mentorship for QMS implementation. Since the start of the mentoring, Laboratory "B" has achieved NIC recognition by WHO, while two other labs made substantial progress and are scheduled for recognition in 2018. In the future, we recommend that mentorship is more inclusive of laboratory directors, and that programs evaluate the amount of staff time needed for mentorship activities, including lab-based assessments and mentoring.